Hubungan antara Work Engagement dengan Turnover Intention pada Pekerja Generasi Milenial di Jabodetabek - Muchtadin Muchtadin (Universitas Negeri Surabaya, 2022)
This study aims to see the extent to which work involvement isinterrelated with turnover intention in millennial generationworkers in Jabodetabek. The method used in this research isquantitative. The data analysis technique used descriptiveanalysis to see the description of the respondents and Pearsoncorrelation analysis was used to see the relationship betweenthe two variables. The sample was taken based on certaincriteria, namely workers who were born in 1982 to 2002,worked in Greater Jakarta and had worked for at least oneyear. Sampling is non-random sampling, namely purposivesampling. A total of 214 millennial workers were collected asrespondents. The results of the study found that the data wasnormally distributed and avoided heteroscedasticity, but thedata was not linear, so bootstrapping had to be done. This studyconcludes that the higher the work engagement, the lower theturnover intention of millennial workers. Future researchshould limit the type of work to millennial workers in theJabodetabek area. Companies must determine differentstrategies in dealing with workers creating millennialgenerations in order to maintain the work involvement of theirworkers so as to reduce turnover intention. Penelitian ini bertujuan untuk melihat sejauh mana work engagement saling berkaitan dengan turnover intention pada pekerja generasi milenial di Jabodetabek. Analisis korelasional dipakai untuk melihat hubungan kedua variabel. Sampel diambil berdasarkan kriteria tertentu yaitu pekerja yang lahir di tahun 1982 sampai 2002, bekerja di Jabodetabek dan sudah bekerja minimal selama satu tahun. Pengambilan sampel bersifat non random sampling yaitu purposive sampling. Sebanyak 214 pekerja milenial dikumpulkan sebagai responden. Hasil penelitian menemukan bawah data berdistribusi normal dan terhindar dari heteroskedastisitas namun data tidak linear sehingga harus dilakukan bootstrap. Penelitian ini menyimpulkan bahwa semakin tinggi work engagement maka semakin rendah turnover intention yang dimiliki oleh pekerja milenial. Penelitian selanjutnya harus membatas jenis pekerjaan pada pekerja milenial di wilayah Jabodetabek. Perusahaan harus menetapkan strategi yang berbeda dalam menghadapi pekerja generasi milenial agar dapat mempertahankan work engagement pekerjanya sehingga mengurangi turnover intention.